A study on incorporation of transpired solar collector in a novel multifunctional PV/Thermal/Daylighting (PV/T/D) panel - Tian, Meng; Yu, Xu; Su, Yuehong; Zheng, Hongfei; Riffat, Saffa (Elsevier, 2018)
When a transparent dielectric compound parabolic concentrator (CPC) PV panel is applied as a skylight in atrium, heat rejection from the PV cells results in both low electrical conversion efficiency and unwanted heat to the atrium in summer, which usually causes a common issue of overheating or increased cooling load for façade and atrium buildings. This paper introduces a novel multifunctional PV/Thermal/Daylighting (PV/T/D) system by incorporating a transpired solar collector with the dielectric CPC panel. The thermal performance of system was investigated through simulations by computational fluid dynamics (CFD) software and experiments. Parametric studies were conducted to evaluate the effects on the thermal performance by different design criteria such as approach velocity, plenum height, pitch and diameter of perforation, porosity and solar radiation level. The experiments were taken under both indoor solar simulator and outdoor real sky conditions. Results show that the designed PV/T/D system could largely remove the heat generated on the PV cells so that the higher PV operation efficiency could be achieved. In addition, the design of transparent perforation plate underneath the dielectric CPC panel could largely reduce the heat flux to the atrium space so that the cooling load of atrium could be largely reduced.